Pengaruh Kepuasan Kerja dan Motivasi Kerja Terhadap Perilaku Organisasi Karyawan UMKM Amara Laundry, Lubuk Begalung, Padang - Yuliana Fransiska; Zilfa Aulia Marsandi; Vivi Nila Sari (Jurnal Ekonomi dan Bisnis Digital, 2024)
The research discusses the development of the Laundry service business in increasing marginal income from an economic perspective. The main problem in this research is how business development is carried out to increase income in the Amara Laundry business. The research aims to determine the business development carried out by Amara Laundry, The contribution of business development carried out by Amara Laundry in increasing household marginal income, and the economic perspective on business development carried out by Amara Laundry. The type of research used is qualitative research with an economic approach. The subjectog this research were Amara Laundry employees, while the research object was the influence of job satisfaction and work motivation on the organization behavior of Amara Laundry ESMES employees. The data collection techniques used are observation, interview and documentation methods. The collected data was then processed and anallyzed using qualitative descriptive techniques